Growth opportunities, default risk, dan corporate social responbility terhadap earning response coefficient dengan good corporate governance sebagai variabel moderasi (Pada perusahaan yang terindeks di IDXBUMN20 bursa efek Indonesia tahun 2018-2020)] - Diarti, Tri Wahyu; Hariyanto, Wiwit (Jurnal Ekonomi, Bisnis dan Pendidikan (JEBP), 2023)
Abstract: This study aims to examine the effect of growth opportunities, default risk, and corporate social responsibility on the earning response coefficient with good corporate governance as a moderating variable. This research method uses quantitative research methods, data collection uses documentation studies in the form of secondary data sources reports and company stock prices indexed on IDXBUMN20 BEI in 2018-2020 obtained by as many as 24 companies. The sampling method used is purposive sampling and obtained as many as 17 companies as a sample company. Data analysis method using SmartPLS. The results of the study stated that the variable of good corporate governance was not able to moderate growth opportunities and corporate social responsibility towards the earning response coefficient. However, good corporate governance can moderate the default risk on the earning response coefficient. Abstrak: Penelitian ini bertujuan untuk menguji pengaruh growth opportunities, default risk, dan corporate social responbility terhadap earning response coefficient dengan good corporate governance sebagai variabel moderasi. Metode penelitian ini menggunakan metode penelitian kuantitatif, pengumpulan data menggukan studi dokumentasi berupa sumber data sekunder laporan serta harga saham perusahaan yang terindeks di IDXBUMN20 BEI tahun 2018-2020 diperoleh sebanyak 24 perusahaan. Metode sampling yang digunakan adalah purposive sampling dan diperoleh sebanyak 17 perusahaan sebagai sampel perusahaan. Metode analisis data menggunakan SmartPLS. Hasil penelitian menyatakan variabel good corporate governance tidak mampu memoderasi growth opportunities dan corporate social responbility terhadap earning response coefficient. Namun good corporate governan mampu memoderasi default risk terhadap earning response coefficient.